Cerenkov Luminescence Tomography of Aminopeptidase N (APN/CD13) Expression in Mice Bearing HT1080 Tumors - Zhenhua Hu; Weidong Yang; Xiaowei Ma; Wenhui Ma; Xiaochao Qu; Jimin Liang; Jing Wang; Jie Tian (Molecular Imaging)
In vivo imaging of aminopeptidase N (APN/CD13) expression is crucial for the early detection of cancer. This study attempted to show that APN/CD13 expression can be imaged and quantified with novel Cerenkov luminescence tomography (CLT). Na 131 I with various activities was placed at different depths in a tissue-mimicking phantom, and various porcine tissues and luminescent images were acquired. The binding of 131 I-NGR with human fibrosarcoma HT1080 and human colon cancer HT-29 cells was detected with Cerenkov luminescence imaging (CLI). Nude mice bearing HT-1080 tumors were imaged after injection with 131 I-NGR using both planar and tomographic CLI methods. The penetration depth increased with ascending activity of Na 131 I. There was a robust linear correlation between the optical signal intensity and the HT1080 cell numbers ( r 2 = .9691), as well as the activity ( r 2 = .9860). The three-dimensional visualization CLT results clearly showed that 131 I-NGR uptake in tumor tissues represented a high expression of the APN/CD13 receptor. CLT also allowed quantifying 131 I-NGR uptake in tumor tissues showing an average activity of 0.1388 ± 4.6788E-6 MBq in tumor tissues. Our study indicated that 131 I-NGR combined with CLT allowed us to image and quantify tumor-associated APN/CD13 expression noninvasively. The promising CLT technique could be potentially used for sensitively evaluating tumor angiogenesis in vivo.